SUBJECT ANALYSIS IN BATU BARA MALAY FOLKLORE - muhammad farizul Umam (Rahis Cendekia Indonesia, 2023)
Subject is a basic concept in linguistics which designates the subject as the main element of the sentence. In Malay, the subject is usually placed at the beginning of the sentence and acts as the subject of the action or situation described in the sentence. This topic is also related to the concept of grammar, which involves the study of how the components of a sentence are related and form a complete and correct sentence structure. The subject is a sentence element that shows the topic of conversation or topic being discussed. Folklore is a story that lives in the midst of society and develops by word of mouth. Folklore has several characteristics, including the way it is conveyed. Basically, folklore is an oral tradition and is a story passed down from generation to generation. The Batu Bara Malay community has a refined civilization and manners. The folklore analyzed in this study is a story entitled